Birds of Bhutan. - Inskipp, Carol; Inskipp, Tim.; Grimmett, Richard (London : Christopher Helm, 1999)
A guide to the ornithology of Bhutan, a country of great physical beauty and, unusually, one with much of its primary forest intact. It covers all 555 species regularly recorded in the country and includes a list of vagrants.
Includes bibliographical references and index.
Keywords: Birds -- Identification. -- Bhutan; Oiseaux -- Identification. -- Bhoutan